Diversity of fruits in Artibeus lituratus diet in urban and natural habitats in Brazil: a review. (March 2020) - Laurindo, Rafael de Souza; Vizentin-Bugoni, Jeferson
Abstract: The great fruit-eating bat ( Artibeus lituratus ) is a large-sized species that forages primarily on fruits. This species is widespread throughout the Neotropics, where it is common in natural areas and also occupies forest patches and cities. In this study, we review the composition of Artibeus lituratus diet in Brazil as well as the size of fruits and seeds, plant geographic origin, and sampling methods used in natural versus urban habitats. We show that Artibeus lituratus is able to consume a higher proportion of exotic fruits with large seeds in urban environments than in natural areas. Fruit diameter was not statistically different between environments, but both fruit and seed diameters are smaller when detected by fecal sampling than by other methods. This difference is likely due to the fact that in natural habitats studies are predominantly based on fecal samples, which hinders the detection of large unswallowed seeds. Consequently, we recommend the use of complementary sampling methods (not only the widely used technique of fecal sorting) in order to produce more accurate descriptions of frugivorous bats' diets. We suggest that the ability to exploit fruits of exotic plant species including the ones with large seeds may be a key trait for the persistence of A. lituratus in urban habitats.